Ensuring compliance with multilateral environmental agreements: a dialogue between practitioners and academia - Beyerlin, Ulrich; Stoll, Peter-Tobias; Wolfrum, Rüdiger (Studies on the law of treaties, 2006)
In this publication, a number of recognized practitioners and scholars undertake to explore the realities and the conceptual underpinnings of environmental compliance mechanisms. In a relatively short period of time, such mechanisms were introduced in a wide range of new and existing environmental regimes. Yet, little is known about their function in practice and their implications. This is puzzling when considering, that the new mechanisms considerably depart from traditional patterns of counteraction and dispute settlement. Instead they build on partnership and cooperation and include a wide range of possible reactions, which range from those having coercive power to supportive measures. Quite a number of those mechanisms and their functioning are explained in the publication in order to lay ground for some cross-cutting analysis, which covers inter alia reporting, inspection and monitoring, supportive financial incentives and the interrelationship between compliance mechanisms and the principle of state responsibility and dispute settlement. Finally the role of non-governmental organizations is addressed. Practitioners and scholars in international environmental affairs and international law more generally will benefit significantly from the inside views and thorough reflection as provided for in this book